At the intersection of gender and generation: Engaging with 'youth' in the CGIAR Research Program on Forests, Trees and Agroforestry - Clendenning, J.; Elias, Marlène; Sijapati Basnett, Bimbika (CGIAR Research Program on Forests, Trees and Agroforestry, 2019)
The purpose of this brief is to identify the critical issues concerning young people in rural areas that hold significance for FTA’s ability to achieve impact at this time of rapid rural transformation; the key questions concerning youth that matter for FTA; and the approaches by which FTA should engage with these issues and questions as a Program. This brief foregrounds key thematic and conceptual issues that will inform the Program’s revised Gender Equality and Social Inclusion Strategy, which will explicitly address generational issues. It begins by describing demographic trends pertaining to youth in the Global South before turning to critical issues related to young women and men in forest, tree and agroforestry landscapes. Finally, it outlines the contours of a youth research agenda for FTA: the value of taking a relational approach to studying young people, and research questions that can form the basis of research on youth in FTA